Pengaruh pemberian pupuk NPK dan kompos terhadap pertumbuhan semai jabon (Anthocephalus cadamba Roxb Miq) pada media tanah bekas tambang emas (tailing) - Basuki Wasis; Dwita Noviani (Jurnal Ilmu Pertanian Indonesia, 2010)
Tailings is one of the waste generated in the gold mining activities that contain nutrients are low. One of the principles for the management of tailings is merevegetasi land disturbed so that the necessary selection of the type that can be developed, in this case Jabon (Anthocephalus cadamba Roxb Miq.) Is one type that is recommended to be developed in the post-mine land revegetation because it is a type of fast-growing and has a high adaptability to various soil types. Experimental design used in this study was factorial design with two factors. The first factor is fertilizer NPK with 4 level and the second factor is the compost with 4 level. The best dose of the combination of the two fertilizer on the growth of seedlings jabon is high NPK fertilizer with compost dose of 15 grams and 10 grams and diameter growth for seedlings jabon, the best dose is the dose of 15 grams of NPK fertilizer and compost 0 grams.